Phosphine resistance in Tribolium castaneum and Rhyzopertha dominica from stored wheat in Oklahoma - Opit, G. P.; Phillips, Thomas W.; Aikins, Michael J.; Hasan, M. M. (My University, 2012)
Phosphine gas, or hydrogen phosphide (PH[subscript 3]), is the most common insecticide applied to durable stored products worldwide and is routinely used in the United States for treatment of bulk-stored cereal grains and other durable stored products. Research from the late 1980s revealed low frequencies of resistance to various residual grain protectant insecticides and to phosphine in grain insect species collected in Oklahoma. The present work, which used the same previously established discriminating dose bioassays for phosphine toxicity as in the earlier study, evaluated adults of nine different populations of red flour beetle, Tribolium castaneum (Herbst), and five populations of lesser grain borer, Rhyzopertha dominica (F.) collected from different geographic locations in Oklahoma. One additional population for each species was a laboratory susceptible strain. Discriminating dose assays determined eight out of the nine T. castaneum populations, and all five populations of R. dominica, contained phosphine-resistant individuals, and highest resistance frequencies were 94 and 98%, respectively. DoseÐresponse bioassays and logit analyses determined that LC99 values were 3 ppm for susceptible and 377 ppm for resistant T. castaneum, and 2 ppm for susceptible and 3,430 ppm for resistant R. dominica. The most resistant T. castaneum population was 119-fold more resistant than the susceptible strain and the most resistant R. dominica population was over 1,500-fold more resistant. Results suggest a substantial increase in phosphine resistance in these major stored-wheat pests in the past 21 yr, and these levels of resistance to phosphine approach those reported for other stored-grain pest species in other countries.
Citation: Opit, G. P., T. W. Phillips, M. J. Aikins, and M. M. Hasan. 2012. “Phosphine Resistance in Tribolium Castaneum and Rhyzopertha Dominica From Stored Wheat in Oklahoma.” Journal of Economic Entomology 105 (4): 1107–14. https://doi.org/10.1603/EC12064.
Opit, G. P., T. W. Phillips, M. J. Aikins, and M. M. Hasan. 2012. “Phosphine Resistance in Tribolium Castaneum and Rhyzopertha Dominica From Stored Wheat in Oklahoma.” Journal of Economic Entomology 105 (4): 1107–14. https://doi.org/10.1603/EC12064.
Keywords: Fumigation; Stored-product; Red flour beetle; Lesser grain borer; Phosphine resistance